A limited overlap of interactions between the bacterial community of water and sediment in wetland ecosystem of the Yellow River floodplain - Han, Zhiguang; Wang, Cong; Lei, Binghai; Hui, Nan; Yu, Yanyan; Shi, Yu; Zheng, Junqiang (Frontiers in Microbiology, 2023)
Aquatic ecosystems in floodplains provide homes for a variety of active bacterial populations. However, the coexistence pattern of bacterial communities is unclear of water and sediment in these ecosystems. Here, we evaluated bacteria's patterns of co-occurrence in the water and sediment of different time dynamics and plant communities of the Yellow River floodplain ecosystem. The results showed that in comparison to water, the α-diversity of the bacterial community was way greater in sediment. The bacterial community structure significantly differed between water and sediment, and there was a limited overlap of interactions between the bacterial community of water and sediment. In addition, bacteria in water and sediment coexisting show different temporal shifts and community assembly patterns. The water selected for specific groups of microorganisms that assemble over time in a non-reproducible and non-random way whereas the sediment environment was relatively stable and the bacterial communities gathered randomly. The structure of bacterial community in the sediment was significantly influenced by the depth and plant cover. The bacterial community in sediment formed a more robust network than those in water to cope with external changes. These findings improved our comprehension of the ecological trends of water and sediment bacterium colonies coexisting enhanced the biological barrier function, the capacity of floodplain ecosystems to provide services and offered support for doing so.